2021
DOI: 10.1080/19382014.2021.1954459
|View full text |Cite
|
Sign up to set email alerts
|

An overview of current advancements in pancreatic islet transplantation into the omentum

Abstract: Pancreatic islet transplantation to restore insulin production in Type 1 Diabetes Mellitus patients is commonly performed by infusion of islets into the hepatic portal system. However, the risk of portal vein thrombosis or elevation of portal pressure after transplantation introduces challenges to this procedure. Thus, alternative sites have been investigated, among which the omentum represents an ideal candidate. The surgical site is easily accessible, and the tissue is highly vascularized with a large surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…An alternative to transplantation is to implant a renewable source of insulin-producing cells [11]. In the initial trials and early stages of clinical trials, pancreatic islet transplants require repeated use of immunosuppressive drugs [12]. The use of these drugs predisposes the patient to a variety of diseases, especially infectious diseases [13].…”
Section: Research Articlementioning
confidence: 99%
“…An alternative to transplantation is to implant a renewable source of insulin-producing cells [11]. In the initial trials and early stages of clinical trials, pancreatic islet transplants require repeated use of immunosuppressive drugs [12]. The use of these drugs predisposes the patient to a variety of diseases, especially infectious diseases [13].…”
Section: Research Articlementioning
confidence: 99%
“…Among the alternatives, the greater omentum has shown promise, both experimentally [ 2 , 23 ] and in human pilot trials [ 24 , 25 ]. The advantages of the omentum include its high vascularization, its easy surgical accessibility, and its large surface area, which allows transplantation of larger and less purified or encapsulated islet grafts and the possibility of graft retrieval, when needed [ 31 ]. However, the most important advantage is that transplantation into the omentum eliminates the risk of direct contact with the recipient’s blood.…”
Section: Discussionmentioning
confidence: 99%
“…41 Additionally, further investigations have shown that the required islet mass to achieve euglycemia is lower in omentum sites compared to intrahepatic locations. 42 In addition to use of optimal transplantation sites, encapsulation methods can also increase cell viability and survival rates. 8 Encapsulation provides a support structure for the islets that mimics the native pancreatic extracellular matrix (ECM) and a physical barrier that prevents graft rejection and innate inflammatory responses.…”
Section: Identifying Clinical Outcomesmentioning
confidence: 99%
“…Hawthorne et al demonstrated that a pancreas graft in the renal capsule in a porcine model showed resistance to hypoxic‐related injury and a shorter recovery time to graft function 41 . Additionally, further investigations have shown that the required islet mass to achieve euglycemia is lower in omentum sites compared to intrahepatic locations 42 …”
Section: Building a Target Product Profile For Ictmentioning
confidence: 99%